Evolution of Condom Use Among a 5-Year Cohort of Female Sex Workers in Zambia - Malama, Kalonde; Price, Matt A.; Sagaon-Teyssier, Luis; Parker, Rachel; Wall, Kristin M.; Tichacek, Amanda; Sharkey, Tyronza; Kilembe, William; Inambao, Mubiana; Spire, Bruno; Allen, Susan (AIDS and behavior, 2022)
Observing sexual behaviour change over time could help develop behavioural HIV prevention interventions for female sex workers in Zambia, where these interventions are lacking. We investigated the evolution of consistent condom use among female sex workers and their clients and steady partners. Participants were recruited into an HIV incidence cohort from 2012 to 2017. At each visit, women received HIV counselling and testing, screening for sexually transmitted infections (STIs) and free condoms. Our outcome was reported consistent (100%) condom use in the previous month with steady partners, repeat clients, and non-repeat clients. Consistent condom use at baseline was highest with non-repeat clients (36%) followed by repeat clients (27%) and steady partners (17%). Consistent condom use between baseline and Month 42 increased by 35% with steady partners, 39% with repeat clients and 41% with non-repeat clients. Access to condoms, HIV/STI counselling and testing promoted positive sexual behaviour change.